Поетична збірка К. Калитко «Катівня. Виноградник. Дім»: темпоральні аспекти змісту та форми - Лавринович, Лілія Богданівна; Lavrynovych, Liliia B. (Київський університет імені Бориса Грінченка, 2018)
У статті досліджено особливості реалізації темпоральних мотивів у поетичній збірці К. Калитко «Катівня. Виноградник. Дім». Концепт часу у її творах по-різному виявляє себе в зображенні минулого, теперішнього та майбутнього. Художня семіотика часу в автора тісно пов’язана з міфопоетичними образами. Основні темпоральні мотиви — роду, дитинства, старості, травматичної пам’яті, тривання, кохання, смерті, вічності. Характерною рисою стилю К.  Калитко є наявність великої кількості тропів, в основі яких — поетичне осмислення часових образів.

The article investigates peculiarities of temporal motifs realization in K. Kalytko’s poetry collection “Torture Chamber. Vineyard. Home”. The  concept of  time in  K.  Kalytko’s works manifests itself in  the  portrayal of the past, present and future (where present stands for the space of anxiety; powerful emotional experience “here-and-now”, even if the source of its experience is already in the past; precariousness of the future). The artistic semiotics of time in K. Kalytko’s works is closely associated with the mythopoetic images which have, in particular, Christian sources. The main motifs, which clustering around the temporal semantics, are the motifs of kin, childhood, old age, traumatic memory, duration, love, death, eternity. The peculiar feature of K. Kalytko’s style is the presence of many tropes (mainly epithets, comparisons, metaphors) based on the poetic comprehension of temporal images.
The collection of poetry “Toture chamber. Vineyard. Home” by Kateryna Kalytko: temporal aspects o meaning ahd form
Keywords: поетика часу; сучасна українська лірика; Катерина Калитко; мотив часу; міфопоетика; темпоральна семантика; temporal poetics; modern Ukrainian lyrics; Kateryna Kalytko; time motif; mythopoetics; temporal semantics